Les Indiens et le droit provincial : rebondissement récent en Cour suprême du Canada - Patenaude, Micheline (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1986)
Section 88 of the Indian Act states that all laws of general application in force in any province are applicable to Amerindians, subject to certain exceptions. In a recent judgment, Dick v. R., commented upon here in, the Supreme Court of Canada gives to this provision an interpretation considered by the author to be incomplete and debatable. She therefore attempts to assess the implications of such interpretation.